Employment and Dividend Policy of the Firm under Risk - Dehez, Pierre (Review of Economic Studies, 1980)
Journal Article Employment and Dividend Policy of the Firm under Risk Get access Pierre Dehez Pierre Dehez Centre for Operations Research and Econometrics Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 47, Issue 3, April 1980, Pages 503–511, https://doi.org/10.2307/2297301 Published: 01 April 1980 Article history Received: 01 November 1978 Accepted: 01 August 1979 Published: 01 April 1980